The effects of book exposure and reading interest on oral language skills of children with and without a familial risk of dyslexia. (28th April 2020) - Caglar‐Ryeng, Ømur; Eklund, Kenneth; Nergård‐Nilssen, Trude
Abstract : The potential role of home literacy environment (HLE) in children's language development has been widely studied. However, data on the HLE of children with familial risk (FR) of dyslexia are limited. In this longitudinal study, we examined (a) whether amount of book exposure and reading interest at age 4 were different in samples of Norwegian FR and no FR‐children, respectively, (b) whether these home literacy‐related factors exerted different effects depending on family‐risk status on vocabulary and grammar skills at school entry age (6 years) and (c) whether they contributed independently to language outcomes at age 6, after controlling for the 4;6‐year language skills. Results showed no significant between‐group differences in book exposure and reading interest. Furthermore, while interest in reading did not affect vocabulary and grammar in either group, book exposure contributed to vocabulary skills only in the FR‐group by school entry. However, this longitudinal association was mediated by lexical skills at age 4;6, implying that the HLE has a positive indirect effect on later language development through its effect on early language. Thus, these findings can be taken to suggest that early intervention including exposure to various book‐reading activities for pre‐school FR‐children with poor expressive vocabulary is worth considering.